2021
DOI: 10.1136/jitc-2020-001660
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of lymphoma by immune checkpoint inhibitors: the role of T cells, NK cells and cytokine-induced tumor senescence

Abstract: BackgroundAlthough antibodies blocking immune checkpoints have already been approved for clinical cancer treatment, the mechanisms involved are not yet completely elucidated. Here we used a λ-MYC transgenic model of endogenously growing B-cell lymphoma to analyze the requirements for effective therapy with immune checkpoint inhibitors.MethodsGrowth of spontaneous lymphoma was monitored in mice that received antibodies targeting programmed cell death protein 1 and cytotoxic T lymphocyte-associated protein-4, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…Induction of senescence (via p16 or p21 upregulation) [26,126] Human cancer cell lines (bladder, melanoma, and breast) IL-2/IL-12/IL-18-stimulated γδ T cells (via secretion of IFN-γ + TNF) Induction of senescence (via p21 upregulation) [109] Human melanoma cell lines Co-culture-derived supernatants from nonclassical monocytes (slanMo) and NK cells (via secretion of IFN-γ + TNF) Induction of senescence (via p21 upregulation) [120] Murine aortic endothelial cells (MAECs) Th17 cells/IL-17A Induction of senescence (via NF-κB/p53/Rb pathway) [124] Human breast cancer cell line IL-32θ Induction of senescence (mechanism unclear) [125] In addition to the direct effects of the cytokines, immune-mediated cancer control and senescence induction can also be achieved and reinforced by the use of immune checkpoint inhibitors [26]. While blocking antibodies directed against LAG-3 and PD-L1 were sufficient to induce senescence in tumor cells, a combination with an adoptive transfer of TAA-specific Th1 cells further increased this effect.…”
Section: Induction Of Senescence and Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…Induction of senescence (via p16 or p21 upregulation) [26,126] Human cancer cell lines (bladder, melanoma, and breast) IL-2/IL-12/IL-18-stimulated γδ T cells (via secretion of IFN-γ + TNF) Induction of senescence (via p21 upregulation) [109] Human melanoma cell lines Co-culture-derived supernatants from nonclassical monocytes (slanMo) and NK cells (via secretion of IFN-γ + TNF) Induction of senescence (via p21 upregulation) [120] Murine aortic endothelial cells (MAECs) Th17 cells/IL-17A Induction of senescence (via NF-κB/p53/Rb pathway) [124] Human breast cancer cell line IL-32θ Induction of senescence (mechanism unclear) [125] In addition to the direct effects of the cytokines, immune-mediated cancer control and senescence induction can also be achieved and reinforced by the use of immune checkpoint inhibitors [26]. While blocking antibodies directed against LAG-3 and PD-L1 were sufficient to induce senescence in tumor cells, a combination with an adoptive transfer of TAA-specific Th1 cells further increased this effect.…”
Section: Induction Of Senescence and Apoptosismentioning
confidence: 99%
“…These findings clearly demonstrated that interfering with negative regulators of the immune system either expressed on certain immune cells (i.e., LAG-3) or on tumor cells (i.e., PD-L1) is able to restore an anti-tumor response that induces protective cancer control through the senescence barrier that leads to a stable growth arrest instead of a complete regression. Recent reports further showed the consequences of immune checkpoint blockade (ICB) on other cell types upon treatment in a mouse lymphoma model [126,127]. The antibodies used for ICB had, for instance, favorable effects on immune cells.…”
Section: Induction Of Senescence and Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore the potential of immunotherapy strategy on WT, cytokine therapy-induced NK cell functions are likely to affect the clinical course of several human malignancies, including neuroblastoma, gastrointestinal sarcoma, and kidney and lung carcinoma [34,35]. In this study, WT patient autologous PBMCs were stimulated by IL-2 combination with IL-15.…”
Section: Journal Of Oncologymentioning
confidence: 99%
“…In this microenvironment, immune response participates in regulating tumor progression. [7][8][9] Immune checkpoint inhibitors as important emerging treatment modality in cancer therapy, particularly programmed cell death-1/ligand-1(PD-1/PD-L1) immune checkpoint inhibitors. 10,11 PD-1 is a key inhibitory receptor expressed by activated T and B cells.…”
Section: Introductionmentioning
confidence: 99%